PENGAWASAN DALAM PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI (PAUD) DESA DI KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Irwan Safari; Isjoni Isjoni; Zulfan Saam (Universitas Riau, 2018)
Early childhood education management achievement determines the quality ofeducation services to the kids who they are in the golden age as crucial times in their life,influencing of their next level education process. The aim of this research is to find out theachievement of early childhood education management in Bengkalis district. The research subfocusesare: 1) curriculum arrangement and application, 2) the human resources utilization, 3)facilities utilization, 4) financial management, and 5) institution network. This is a descriptivequalitative research, located at PAUD Kasih Bunda of Teluk Latak village and PAUD CahayaInsan Penebal village of Bengkalis district. The data was gained through interview, observation,and document analizing. The informans are manegers, teachers, society man, parents, andnonformal early childhood education controller of Bengkalis district. Then, the collecting datawas analized by interpretative approach.The results of this study shows that the curriculummanagement and application at both PAUD Kasih Bunda and PAUD Cahaya Insan could becategorized good, eventhough parents don’t get contribution in teaching material development.Human resources which consist of the manegers, teachers of both early childhood educationinstitutions are not categorized as academic standard provided. Then, both institutions of earlychildhood education has equiped faciclities for learning process, but it concerns to the lack ofsafety, not confortable, and healthy standard for the kids. Administration staff is not profesionalyet, so that the financial management is not accuntable and transparancy. And the last found ofboth institutions have networking to somes small authorities in the villages without programsand written commitments.